Corruption India's enemy within - Srivastava, C P (Delhi Macmillan, 2001)
This book focuses mainly on the problem of corruption and attempts to explain why our country is gripped in its vicious stranglehold.It attempts to assess the extent of damage caused and it analysis the history of corruption by tracing its origin.
Keywords: Public administration; Political corruption; Indian administrative services-Corrupt